The Foreign Policy of the United States Towards Brazil: Changes and Continuities in Biden's Administration - Morales-Ruvalcaba, Daniel (2021)
During his first two years as president of Brazil, Jair Bolsonaro gave the relationship with the United States the highest priority, achieving an extraordinary understanding with President Donald Trump. However, the arrival of Joseph Biden to the presidency has had a significant impact on that understanding. Here it is shown that the Brazilian-American relations with Presidents Trump and Bolsonaro were framed in their populist government programs and that they were driven by their mutual personal understanding, altering the priorities (but not the content) of the bilateral agenda. The arrival of Biden and his ideological distancing from Bolsonaro does not necessarily imply a cooling in the bilateral relationship, but rather a redirection to institutional channels thanks to the pre-existing mechanisms between the United States and Brazil, as well as a return to historical priorities: economic affairs first, then energy and environmental issues, later military cooperation and finally social topics. In this research, the deductive methodology has been implemented in the study of two dimensions: a discursive one, by examining the most important official speeches of Trump, Bolsonaro and Biden in Brazilian-American relations, with the aim of identifying changes in their perceptions and priorities; and another historical one, when studying the performance of bilateral institutions in the aforementioned areas, in order to detect continuity patterns that go beyond presidential administrations.